A Local Reduction in Cortical GABAergic Synapses after a Loss of Endogenous Brain-Derived Neurotrophic Factor, as Revealed by Single-Cell Gene Knock-Out Method - Kohara, Keigo (J Neurosci, 2007)
To address questions of whether brain-derived neurotrophic factor (BDNF) released from active excitatory neurons acts locally only on GABAergic presynaptic terminals contacting these neurons or generally also on GABAergic terminals contacting other inactive neurons, we developed a single-cell gene knock-out method in organotypic slice culture of visual cortex of floxed BDNF transgenic mice. A biolistic transfection of Cre recombinase with green fluorescence protein (GFP) plasmids to layer II/III of the cortex resulted in loss of BDNF in a single neuron or a small number of neurons, which expressed GFP at 13–14 d in vitro. Analysis with in situ hybridization and immunohistochemistry confirmed that neurons expressing GFP lacked BDNF mRNA and protein, respectively. Analysis with immunohistochemistry using antibody against GABA synthesizing enzyme showed that the number of GABAergic terminals on the soma of BDNF knock-out neurons was smaller than that of neighboring control neurons. Morphological analysis indicated that there was no significant difference in the soma size and branch points and length of dendrites between the BDNF knock-out and control neurons. Recordings of miniature IPSCs (mIPSCs) showed that the frequency of mIPSCs of BDNF knock-out neurons was lower than that of control neurons, although the amplitude was not significantly different, suggesting the smaller number of functional GABAergic synapses on whole the BDNF knock-out neuron. The present results suggest that BDNF released from postsynaptic target neurons promotes the formation or proliferation of GABAergic synapses through its local actions in layer II/III of visual cortex.